2018
DOI: 10.3389/fphys.2018.00578
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Attenuates DOCA-Salt Hypertension: Effects on Vascular Tone

Abstract: Inflammation is increasingly recognized as a driver of hypertension. Both genetic and pharmacological inhibition of B and T cells attenuates most forms of experimental hypertension. Accordingly, the immunosuppressive drug mycophenolate mofetil (MMF) reduces blood pressure in the deoxycorticosterone acetate (DOCA-) salt model. However, the mechanisms by which MMF prevent hypertension in the DOCA-salt model remain unclear. Recent studies indicate that immunosuppression can inhibit sodium transporter activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
4
6
0
Order By: Relevance
“…Abundant evidence has demonstrated the association between gut dysbiosis, the immune system, and hypertension [1,3,4,11,43]. Our results are consistent with data previously described, with MMF being able to prevent BP increase [17,18] and improve aortic endothelial dysfunction, increasing NO availability in DOCA-salt animals [18]. Furthermore, we found that the MMF treatment induced a modulation in the aortic immune cell infiltration, inducing a reduction in the pro-inflammatory and pro-oxidative cytokine profile.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Abundant evidence has demonstrated the association between gut dysbiosis, the immune system, and hypertension [1,3,4,11,43]. Our results are consistent with data previously described, with MMF being able to prevent BP increase [17,18] and improve aortic endothelial dysfunction, increasing NO availability in DOCA-salt animals [18]. Furthermore, we found that the MMF treatment induced a modulation in the aortic immune cell infiltration, inducing a reduction in the pro-inflammatory and pro-oxidative cytokine profile.…”
Section: Discussionsupporting
confidence: 92%
“…As was described previously [18], chronic MMF treatment showed a progressive decrease in SBP ( Figure 5A), which was significant after 2 weeks of treatment, reaching a total reduction of 22.3 ± 3.4 mmHg in the DOCA-salt group. MMF induced a significant reduction of left ventricular hypertrophy (≈13%) in the DOCA-salt group ( Figure 5B).…”
Section: Mycophenolate Mofetil (Mmf) Reduced Bp Improves the Vasculasupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, in SLE mice receiving treatment with MMF, CD45R + B cells depletion with subsequent autoantibody production inhibition was observed. These findings are connected to a previous study that linked autoimmunity with HTN development [181]. Hypertensive patients tend to have an increased level of AT1R antibodies, α -adrenergic receptors, and L-type voltage gated calcium channels [180183].…”
Section: Inflammation As a Potential Therapeutic Target In Arteriasupporting
confidence: 85%